Respuesta :

14.a. (2x+2)(5-x^2)
2x+2=0
2x=-2
x=-1

5-x^2=0
x^2=5
x=square root of 5

Therefore x=-1, square root of 5

14.b. f(x)= (2x+2)(5-x^2)
=10x+10-2x^3-2x^2
=-2x^3-2x^2+10x+10

Answer:

The answer to your question is below

Step-by-step explanation:

14a           f(x) = (2x + 2)(5 - x²)

Process

1.- Factor (5 - x²)

               (5 - x²) = ([tex](\sqrt{5} - x)(\sqrt{5} + x)[/tex]

Then        f(x) = (2x + 2) ([tex](\sqrt{5} - x)(\sqrt{5} + x)[/tex]

2.- Equal each factor to zero

               2x₁ + 2 = 0            [tex]\sqrt{5}[/tex] - x₂ = 0            [tex]\sqrt{5} + x[/tex]₃ = 0

               2x₁ = -2                  x₂ = [tex]\sqrt{5}[/tex]                 x₃ = -[tex]\sqrt{5}[/tex]

                 x₁ = -2/2

                 x₁ = -1

3.- Conclusion

     The roots of the function are

      x₁ = -1

      x₂ = [tex]\sqrt{5}[/tex]

      x₃ = - [tex]\sqrt{5}[/tex]

14b.Expand the function

             (2x + 2) (5 - x²) = 10x - 2x³ + 10 - 2x²

or                                      -2x³ - 2x² + 10x + 10

ACCESS MORE